Pengaruh Ukuran Perusahaan, Kompleksitas Operasi, Audit Tenure, Opini Audit, dan Audit Switching terhadap Audit Delay pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Azhari, Fajrul (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study examines the effects of firm size, operating complexity, audit tenure, audit opinion, and auditor switching on audit delay in property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2021 period. The study employs a quantitative approach using secondary data obtained from audited annual financial statements. The sample was selected through purposive sampling and consisted of 57 companies, resulting in 171 firm-year observations. Audit delay was measured using a dummy variable, while firm size was measured using the natural logarithm of total assets, operating complexity was measured by the number of subsidiaries, audit tenure was measured by the consecutive number of engagement years, and audit opinion and auditor switching were measured using dummy variables. Data were analyzed using logistic regression with EViews version 12. The results show that firm size, operating complexity, and audit opinion significantly affect audit delay. In contrast, audit tenure and auditor switching do not have significant effects. Simultaneously, the five independent variables significantly affect audit delay. The McFadden R-squared value is 34.0%, indicating that the model explains 34.0% of the variation in audit delay.